Thai EFL Business Majors’ Metacognitive Awareness when Reading Online Texts - Chomphuchart, Nuwee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The purpose of this study was to examine Thai EFL Business majors’ metacognitive awareness when reading school-related online texts in English. The surveyed participants were 582 male and female students from 12 universities across Thailand. Twelve students were selected for an in-depth study based on a purposeful sampling of the maximum variation. Major data sources included a Metacognitive Awareness Questionnaire designed by Carrell (1989), think-aloud protocols, retrospective interviews, and observation. The quantitative results demonstrated that the participants used a combination of metacognitive awareness strategies. Two factors affected the use of metacognitive awareness: the institutional type and the demographic area. In addition, the qualitative results showed that the type of institution might have an effect on the participants’ strategy use.